An FN method for the radiative transport equation in three dimensions. (23rd July 2015) - Machida, Manabu
Abstract: The F N method is an accurate and efficient numerical method for the one-dimensional radiative transport equation. In this paper the F N method is extended to three dimensions using rotated reference frames. To demonstrate the method, the exiting flux from structured illumination reflected by a medium occupying the half space is calculated.